EQUIPMENT FOR NONDESTRUCTIVE TESTING OF SILICON WAFERS SUBMICRON TOPOLOGY DURING THE FABRICATION OF INTEGRATED CIRCUITS - S. A. Chizhik; S. P. Basalaev; V. A. Pilipenko; A. L. Khudoley; T. A. Kuznetsova; V. V. Chikunov; A. A. Suslov (Приборы и методы измерений)
The advantages of using an atomic force microscopy in manufacturing of submicron integrated circuits are described. The possibilities of characterizing the surface morphology and the etching profile for silicon substrate and bus lines, estimation of the periodicity and size of bus lines, geometrical stability for elementary bus line are shown. Methods of optical and atomic force microcopies are combined in one diagnostic unit. Scanning  probe  microscope  (SPM  200)  is  designed  and  produced.  Complex  SPM  200  realizes  nondestructive control of microelectronics elements made on silicon wafers up to 200 mm in diameter and it is introduced by JSC «Integral» for the purpose of operational control, metrology and acceptance of the final product.